Anti-ulcer activity of polyphenols of Eleusinian corocana (L.) Gaertn, in Aspirin plus pyloric ligation induced gastric ulcer in Wistar albino rats (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2026)
The polyphenols of Eleusinian corocana (L.) Gaertn have various nutraceutical and therapeutic values in human health. It has been reported to possess potent anti-inflammatory, antioxidant, antimicrobial, antidiabetic, and gastroprotective effects. However, there is no experimental evidence to reveal its gastroprotective action. The present study was carried out to evaluate the protective effect of polyphenols from Ragi (PPR) against Aspirin plus pyloric ligation-induced gastric ulcers in Wistar albino rats. The Aspirin plus pyloric ligation induced a significant increase in the ulcer index, pH, total and free acidity of the gastric juice in the ulcer control group rats. Macroscopic examination of the internal aspects of stomach tissue in the ulcer control group rats showed more severe mucosal erosion, with large areas of haemorrhagic streaks. Histopathological examination of stomach tissue showed marked destruction of the epithelial layer (EL), submucosal oedema, cell infiltration, and severe congestion of blood vessels in ulcer control rats. Pre-treatment with polyphenols of Ragi and Pantoprazole significantly reduced pH (p